Commentary on the Old Testament ; v. 4 - Keil, Johan Karl Friedrich, 1807-1888; Delitzsch, Franz Julius, 1813-1890; Bolton, Francis (Grand Rapids, MI Eerdmans)
Contents : v. 4 : Job / F. Delitzsch. Includes bibliographical references.
Reprinted 1975.
Keywords: Bible. O.T. -- commentaries